Effect of β radiation on success of glaucoma drainage surgery in South Africa: randomised controlled trial. Issue 7575 (5th October 2006) - Kirwan, James F; Cousens, Simon; Venter, Lynette; Cook, Colin; Stulting, Andries; Roux, Paul; Murdoch, Ian
Abstract: Objective To evaluate whether β radiation may offer a practical method of improving surgical success for glaucoma drainage surgery in South Africa. Design Double blind, randomised controlled trial. Setting Three public hospitals in South Africa. Participants 450 black Africans with primary glaucoma. Interventions Trabeculectomy with 1000 cGy β radiation or standard trabeculectomy without β radiation (placebo). Main outcome measures Primary outcome measure was surgical failure within 12 months (intraocular pressure > 21 mm Hg while receiving no treatment for ocular hypotension). Secondary outcomes were visual acuity, surgical reintervention for cataract, and intraoperative and postoperative complications. Results 320 people were recruited. β radiation was given to 164; 20 (6%) were not seen again after surgery. One year after surgery the estimated risk of surgical failure was 30% (95% confidence interval 22% to 38%) in the placebo arm compared with 5% (2% to 10%) in the radiation arm. The radiation group experienced a higher incidence of operable cataract (18 participants) than the placebo group (five participants; P = 0.01). At two years the estimated risks with placebo and β radiation were, respectively, 2.8% (0.9% to 8.3%) and 16.7% (10.0% to 27.3%). Conclusion β radiation substantially reduced the risk of surgical failure after glaucoma surgery. Some evidence was, however, found of an increased risk for cataract surgery (a known complication of trabeculectomy) in the β radiation arm during the two years after surgery. Trial registration ISRCTN62430622 [controlled-trials.com] .